2001
DOI: 10.1099/0022-1317-50-1-62
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serological markers for the immunodiagnosis of acute acquired toxoplasmosis

Abstract: The detection of speci®c IgM antibodies has been the most frequently used serological marker for diagnosing recent toxoplasmosis. However, the persistence of speci®c IgM antibodies in some patients and the use of tests with a low speci®city have complicated the interpretation of serological results when toxoplasmosis is suspected. The purpose of the present study was to determine the value of newer serological techniques in the diagnosis of acute acquired toxoplasmosis. Sixty-four sera, 31 from patients with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 14 publications
1
39
0
8
Order By: Relevance
“…Both tests had low values at the early time of infection (HS \100 IU/ml and AC, 50 IU/ml) then both values increased to attain plateau level. In the present study, the AC titer attained high level early in the infection being caused by the proliferating tachyzoites (Montoya and Remington 1995;Suzuki et al 2001;Montoya et al 2007). On the other hand, the HS-test still rises up late, as previously reported in humans where high HS-titers are characterizing chronic infections (Suzuki et al 1988;Dannemann et al 1990;Montoya et al 2007).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Both tests had low values at the early time of infection (HS \100 IU/ml and AC, 50 IU/ml) then both values increased to attain plateau level. In the present study, the AC titer attained high level early in the infection being caused by the proliferating tachyzoites (Montoya and Remington 1995;Suzuki et al 2001;Montoya et al 2007). On the other hand, the HS-test still rises up late, as previously reported in humans where high HS-titers are characterizing chronic infections (Suzuki et al 1988;Dannemann et al 1990;Montoya et al 2007).…”
Section: Discussionsupporting
confidence: 50%
“…The Toxoplasma agglutination test is very simple, rapid and does not require special technique to prepare the antigen neither special equipments nor apparatus to be carried on (Suzuki et al 2001). The use of sensitive antigenic preparation and adding 2-Mercaptoethanol improves its specificity and sensitivity, to parallel those of the dye test (Desmonts and Remington 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some serological tests use live agents (Sabin Feldman assay), intact parasites, as indirect immunofluorescence assays or whole extracts in enzymatic immunosorbent assays to detect the presence of specific IgM for definition of acute (less than one year) infections during screening for treatment (REMINGTON et al, 2006). The development of commercial assays and the use of ultra-sensitive techniques such as IgM capture tests increased the sensitivity of these assays, but resulted in extended periods of IgM presence after acute infections, with consequent loss of screening efficiency (SUZUKI et al, 2001). IgG avidity was introduced for temporal definition of viral infection in rubella (LEHTONEN & MEURMAN, 1982), and was adapted to toxoplasmosis to distinguish recent and old infections (HEDMAN et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the avidity of antibody IgG is a good index of the time of the infection, defining if the acute infection has occurred in the past few months despite conflicting results between tests (BARBERI et al, 2001). Recombinant antigens were frequently tested in serology for toxoplasmosis (SUZUKI et al, 2001), usually with adequate but weak screening results compared to whole extracts in ELISA ( VAN GELDER et al, 1993 (BEGHETTO et al, 2003). Most of these studies were performed on selected sera panels defined by other tests, which could interfere in efficacy determination.…”
Section: Introductionmentioning
confidence: 99%